If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(-3x-7)=6(x+7)+4
We move all terms to the left:
8(-3x-7)-(6(x+7)+4)=0
We multiply parentheses
-24x-(6(x+7)+4)-56=0
We calculate terms in parentheses: -(6(x+7)+4), so:We get rid of parentheses
6(x+7)+4
We multiply parentheses
6x+42+4
We add all the numbers together, and all the variables
6x+46
Back to the equation:
-(6x+46)
-24x-6x-46-56=0
We add all the numbers together, and all the variables
-30x-102=0
We move all terms containing x to the left, all other terms to the right
-30x=102
x=102/-30
x=-3+2/5
| n/10+8=15. | | 10+10j=8j | | 54+x+89/3=79 | | b−3=3 | | 2(5y+3)=3y-22 | | 5x+6=51. | | -n-7=-2n | | -1-(-7)=x/10 | | 4^x=19/15 | | X/3-5=3*x-2) | | 8−2(3−x)=4x+68-23-x=4x+6 | | –12d–6=–2(d+3)–10d | | 2(5y=3)=3y-22 | | 2x=84. | | -12d-6=-2(d+3)-10d | | -1-(-7)=x|10 | | 7-5m=-6m | | 2x+1/6x=13 | | -7c+10=-9c | | 38=28-2(x+1) | | 5(n+3)=-55-6(n-8) | | -7+5j=7j+7 | | -10=v/4+2 | | -17-u-3=-2 | | 10x+20=16x+4 | | 5h-8=4h | | -2p+10=-10+10p-2p | | -9-z=1-2z | | 14(d+6)=4(d-3)+10d | | 55=43+v | | 4x+12=320 | | -16+2q=q |